Apoyo en las actividades de gestión ambiental enfocadas en la categoría élite del PREAD para la empresa Challenger S.A.S en el año 2022 (2022)
The internship is carried out in the company Challenger S.A. S with the need for a renewal in the matrix of environmental impacts that would allow to deepen and further emphasize the separate controls, starting with the Source that seeks to give an adequate separation of waste from each area of the company, then by the Environment that consists of reviewing the comprehensive plans to ensure proper disposal of each waste produced and finally to the Individual who is sensitized through dialogue on proper use of waste to all staff in each of the areas of Challenger S. A. S. A.S. such as the refrigeration area, logistics, electronics, administrative, furniture and gas appliances with the objective of focusing on supporting from the environmental management all the processes oriented to the PREAD audit.